Information Systems and Sustainable Supply Chains in Makassar Coffee Shops - Febrianto Kurniawan Djihan; Bryan Michio Ng; Sachio Sutedja; Michael Gilbert Galla; Christian Archie; Firman, Afrizal (Business and Entrepreneurial Review, 2025)
This research examines the role of management information systems (MIS) in enhancing organizational performance through improved stock management in coffee shops. The Study aims to investigate the direct effect of MIS on organizational outcomes and the mediating effect of inventory management. A quantitative method using survey was employed, involving 126 employees engaged in inventory operations in the Makassar coffee industry. Data were analyzed using regression and Path analysis. The results reveal that MIS significantly enhances stock accuracy, reduces operational delays, and improves employee productivity. Real Time analytics play a pivotal role in minimizing stockout incidents, thereby increasing satisfaction. This study contributes by proposing an integrative model for stock monitoring Using MIS as a strategic tool to support sustainable supply chain operations in the coffee retail industry.